Pengaruh Kompetensi Sumber Daya Manusia Dan Moralitas Individu Terhadap Pencegahan Fraud Dalam Pengelolaan Dana Desa: (Studi Kasus pada Desa Tou Timur, Desa Pise, Desa Kota Baru Dan Desa Tou Kecamatan Kota Baru Kabupaten Ende) - Emiliana Londa; Henrikus Herdi; Wihelmina Maryetha Yulia Jaeng (Universitas Maritim AMNI Semarang, 2023)
This study aims to analyze the effect of human resource competence and individual morality on fraud prevention in village fund management. The sampling technique uses a purposive sampling technique. The data source used in this study is primary data, namely data obtained directly from respondents using a questionnaire. The sample in this study amounted to 40 respondents. Data processing in this study used the SPSS program. This study uses quantitative methods with multiple linear regression analysis techniques and hypothesis testing using the f test and t test. The results of this study indicate that human resource competence (X1) has a significant effect on fraud prevention in managing village funds (Y). Meanwhile, individual morality (X2) has a significant influence on fraud prevention in managing village funds (Y). Simultaneously the two independent variables, namely the competence of human resources and individual morality, simultaneously affect the dependent variable, namely the variable of fraud prevention in managing village funds.